COVID-19: PHARMACOLOGICAL AND THERAPEUTIC APPROACHES - Ghoneim, Mai ES.; Ali, Bassma M.; Khalifa, Asmaa A. (Universal Journal of Pharmaceutical Research, 2021)
In the end of 2019, SARS-CoV-2, a new virus from Corona viruses family, has been detected in China and was responsible for COVID-19 disease. This disease has been suddenly and vigorously disseminated among individuals all over the world. Based on genetic vicinity, this novel virus is similar to SARS-CoV and MERS-CoV and it can spread from an unknown animal host to individuals. Many published clinical data and in vitro studies may offer treatment strategies of some effective antiviral and repurposed drugs, including remdesivir, favipiravir, lopinavir/ritonavir, corticosteroids, etc. This narrative review describes current pharmacological proposed treatments for COVID-19 patients and available experimental and clinical studies for these drugs. Eventually, these data may help to explain the most preferable way to treat COVID-19 and lessen the accompanied symptoms and complications. Peer Review History: Received 3 October 2020; Revised 12 November; Accepted 26 December; Available online 15 January 2021 Academic Editor: Prof. Cyprian Ogbonna ONYEJI , Obafemi Awolowo University, Ile-Ife, Nigeria, conyeji@oauife.edu.ng Reviewer(s) detail: Dr. DANIYAN Oluwatoyin Michael , Obafemi Awolowo University, ILE-IFE, Nigeria, toyinpharm@gmail.com Dr. George Zhu , Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com Dr. Nuray Arı , Ankara University, Turkiye, ari@ankara.edu.tr